Pengaruh Media Tanam Organik dan Anaorganik terhadap Pertumbuhan Seledri (Apium graveolens L) dengan Sistem Hidroponik DFT - Muhiddin, Nurmita; Lahming; Lestari, Nunik (Agricultural Technology Education Study Program, 2023)
Celery is a green leafy plant that is often used as a traditional herb and vegetable. The purpose of this study was to determine the best organic or inorganic growing media for celery plant growth using the DFT system hydroponic cultivation technique. The organic growing media used were coconut coir and fern roots. For inorganic planting media in the form of rockwool and broken bricks. The method used is a completely randomized design using ANOVA data analysis technique with Duncan's further test. The research data obtained during observations showed that the P3 treatment of rockwool growing media was the best treatment with an average number of leaves (63.67 pieces), plant height (27.83 cm), leaf width (4.57 cm), plant fresh weight ( 36 g), plant dry weight (2.16 g), chlorophyll a content (18.7 mg/g), chlorophyll b content (7.5 mg/g) and total chlorophyll (26.28 mg/g). The advantages of inorganic planting media (rockwool) are that it has a higher aeration rate, is not too humid so it does not rot easily and is guaranteed to be sterilized and does not contain disease oniclum